2013
DOI: 10.1371/journal.pone.0063265
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Functions Pleiotropically in Differentiation and Tumorigenesis in Mouse Embryo-Derived Stem Cells

Abstract: The canonical Wnt/β-catenin signaling pathway plays a crucial role in the maintenance of the balance between proliferation and differentiation throughout embryogenesis and tissue homeostasis. β-Catenin, encoded by the Ctnnb1 gene, mediates an intracellular signaling cascade activated by Wnt. It also plays an important role in the maintenance of various types of stem cells including adult stem cells and cancer stem cells. However, it is unclear if β-catenin is required for the derivation of mouse embryo-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
(63 reference statements)
3
13
0
Order By: Relevance
“…However, further experiments challenged the two simplest conclusions from these studies: that β-catenin is required for pluripotency and that this function acts via its transcriptional activity. β-catenin is not required for the establishment of pluripotency as ES cells can be derived from β-catenin mutant blastocysts [101] and, more significantly, β-catenin mutant cells can be maintained in culture, albeit with a certain degree of instability [29,33,85,102104]. In addition, functional analysis of β-catenin activity in ES cells revealed that its transcriptional activity is dispensable for pluripotency [33,102,103].…”
Section: Function Of Wnt/β-catenin Signalling In Embryonic and Epimentioning
confidence: 99%
“…However, further experiments challenged the two simplest conclusions from these studies: that β-catenin is required for pluripotency and that this function acts via its transcriptional activity. β-catenin is not required for the establishment of pluripotency as ES cells can be derived from β-catenin mutant blastocysts [101] and, more significantly, β-catenin mutant cells can be maintained in culture, albeit with a certain degree of instability [29,33,85,102104]. In addition, functional analysis of β-catenin activity in ES cells revealed that its transcriptional activity is dispensable for pluripotency [33,102,103].…”
Section: Function Of Wnt/β-catenin Signalling In Embryonic and Epimentioning
confidence: 99%
“…β-Catenin is the key downstream effector in the Wnt/β-catenin pathway, activation of which leads to the accumulation of β-catenin in the nucleus [25]. Previous studies report involvement of the Wnt/β-catenin pathway in early embryonic development and tumorigenesis [26]. Interestingly, elements of the Wnt/β-catenin pathway are mutated in approximately 90% of CRCs [25] and high levels of nuclear β-catenin have been correlated with a poor prognosis in CRC patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…These results are perhaps surprising in view of reports implicating Jarid2 in the regulation of Notch1 ( Mysliwiec et al., 2011 ), or showing that Nanog represses the expression of Dkk1 (a secreted Wnt inhibitor) in ESCs to enhance β-catenin expression ( Marucci et al., 2014 ). Current literature contains many conflicting reports on whether β-catenin is essential or dispensable for maintaining ESC pluripotency ( Okumura et al., 2013; Soncin et al., 2009; ten Berge et al., 2011; Wray et al., 2011; Ying et al., 2008 ). This discrepancy probably reflects the fact that β-catenin is pleotropic and regulates both gene transcription and cell adhesion (reviewed in Brembeck et al., 2006 and Heuberger and Birchmeier, 2010 ).…”
Section: Discussionmentioning
confidence: 99%